Differing associations between sex determination and sex-linked inversions in two ecotypes of Littorina saxatilis. Issue 5 (1st October 2022) - Hearn, Katherine E.; Koch, Eva L.; Stankowski, Sean; Butlin, Roger K.; Faria, Rui; Johannesson, Kerstin; Westram, Anja M.
Abstract: Sexual antagonism is a common hypothesis for driving the evolution of sex chromosomes, whereby recombination suppression is favored between sexually antagonistic loci and the sex-determining locus to maintain beneficial combinations of alleles. This results in the formation of a sex-determining region. Chromosomal inversions may contribute to recombination suppression but their precise role in sex chromosome evolution remains unclear. Because local adaptation is frequently facilitated through the suppression of recombination between adaptive loci by chromosomal inversions, there is potential for inversions that cover sex-determining regions to be involved in local adaptation as well, particularly if habitat variation creates environment-dependent sexual antagonism. With these processes in mind, we investigated sex determination in a well-studied example of local adaptation within a species: the intertidal snail, Littorina saxatilis . Using SNP data from a Swedish hybrid zone, we find novel evidence for a female-heterogametic sex determination system that is restricted to one ecotype. Our results suggest that four putative chromosomal inversions, two previously described and two newly discovered, span the putative sex chromosome pair. We determine their differing associations with sex, which suggest distinct strata of differing ages. The same inversions are found in the second ecotype but do not show any sex association. The striking disparity in inversion-sex associations between ecotypes that are connected by gene flow across a habitat transition that is just a few meters wide indicates a difference in selective regime that has produced a distinct barrier to the spread of the newly discovered sex-determining region between ecotypes. Such sex chromosome-environment interactions have not previously been uncovered in L. saxatilis and are known in few other organisms. A combination of both sex-specific selection and divergent natural selection is required to explain these highly unusual patterns.